Evolution of short-range to long-range monoclinic order of MB type with decreasing temperature in 0.75[Pb(Mg1/3Nb 2/3)O3]-0.25PbTiO3 - Singh, A.K.; Pandey, D.; Zaharko, O. (My University, 2006)
Results of Rietveld analysis of powder neutron diffraction data on 0.75 [Pb (Mg13 Nb23) O3] -0.25PbTi O3 (PMN-0.25PT) at room temperature and 80 K are presented. It is shown that the currently believed structural model based on average rhombohedral structure (space group R3m) with local 〈110〉 disordered Pb atoms cannot account for the structure of PMN-0.25PT at 80 K. The low temperature structure of PMN-0.25PT is best refined using Cm space group of MB type. It is argued that with decreasing temperature the short-range monoclinic order at 300 K grows into a truly long-range ordered monoclinic structure at 80 K.
Keywords: Neutron diffraction; Monoclinic structure; Lead compounds